Acetylation of TBX5 by KAT2B and KAT2A regulates heart and limb development - Ghosh, Tushar K.; Aparicio-Sánchez, José J.; Buxton, Sarah; Ketley, Ami; Mohamed, Tasabeeh; Rutland, Catrin S.; Loughna, Siobhan; Brook, J. David (Elsevier, 2018)
TBX5 plays a critical role in heart and forelimb development. Mutations in TBX5 cause Holt-Oram syndrome, an autosomal dominant condition that affects the formation of the heart and upper - limb. Several studies have provided significant insight into the role of TBX5 in cardiogenesis; however, how TBX5 activity is regulated by other factors is still unknown. Here we report that histone acetyltransferases KAT2A and KAT2B associate with TBX5 and acetylateit at Lys339. Acetylation potentiates its transcriptional activity and is required for nuclear retention. Morpholino-mediated knockdown of kat2a and kat2b transcripts in zebrafish severely perturb heart and limb development, mirroring the tbx5a knockdown phenotype. The phenotypes found in MO-injected embryos were also observed when we introduced mutations in the kat2a or kat2b genes using the CRISPR-Cas system. The sestudies highlight the importance of KAT2A and KAT2B modulation of TBX5 and their impact on heart and limb development